ClpB/Hsp100 proteins and heat stress tolerance in plants. (2nd September 2016) - Mishra, Ratnesh Chandra; Grover, Anil
Abstract: High-temperature stress can disrupt cellular proteostasis, resulting in the accumulation of insoluble protein aggregates. For survival under stressful conditions, it is important for cells to maintain a pool of native soluble proteins by preventing and/or dissociating these aggregates. Chaperones such as GroEL/GroES (Hsp60/Hsp10) and DnaK/DnaJ/GrpE (Hsp70/Hsp40/nucleotide exchange factor) help cells minimize protein aggregation. Protein disaggregation is accomplished by chaperones belonging to the C aseino l ytic P rotease (Clp) family of proteins. ClpB/Hsp100 proteins are strikingly ubiquitous and are found in bacteria, yeast and multi-cellular plants. The expression of these proteins is regulated by heat stress (HS) and developmental cues. Bacteria and yeast contain one and two forms of ClpB proteins, respectively. Plants possess multiple forms of these proteins that are localized to different cellular compartments (i.e. cytoplasm/nucleus, chloroplast or mitochondria). Overwhelming evidence suggests that ClpB/Hsp100 proteins play decisive roles in cell adaptation to HS. Mutant bacteria and yeast cells lacking active ClpB/Hsp100 proteins are critically sensitive to high-temperature stress. Likewise, Arabidopsis, maize and rice mutants lacking cytoplasmic ClpB proteins are very sensitive to heat. In this study, we present the structural and functional attributes of plant ClpB forms.